Human Resources after Merger and Acquisition in Prabhu Bank - Upadhyaya, Prashant (NPRC Journal of Multidisciplinary Research, 2024)
The unnatural increment of the Nepalese Banking and Financial Industries (BFIs) has brings several financial challenges and complications in the financial market. The financial indicator had indicated that the Nepalese financial sector was weak, vulnerable and at the verge of a collapse. Regularity body in Nepal having difficulties in regulation, with the coordination with Nepal Rastra Bank (NRB), Nepalese government lunched the Monitory Policy on 2072/73 especially focusing on capital growth of the BFIs. Merger and Acquisition (M&A) play a vigorous role in the after the Nepal Rastra Bank implemented the Merger Bylaws Policy, Banking and Financial Institutions (BFIs) in the Nepalese Market focus on M&A with appropriate partners. The increasing trends of M&A without proper guidance and experience gradually increase challenge on both stability and operational issues in Prabhu bank. Mostly Human resources form the Bank are persecute after the post-merger activity in the institutions. Therefore, this paper presents the issues on HRM among Prabhu Bank after M&A. This study uses a qualitative research design with 35 participants. Data is gathered through interviews, and the findings are determined by thematic analysis. The results of the study show that while mergers create chances for employees to grow professionally, collaborate across different cultures, and feel a sense of stewardship, similarly highlight difficulties like identity loss and communication gaps, Leadership Uncertainty and increase competitive behavior among peers which ultimate effect on the growth of both employee and the organization. The study concludes that mergers provide chances for staff growth and collaboration, and effective integration requires addressing identity issues and communication barriers. Post-merger human resource management issues within Prabhu Bank.